2021
DOI: 10.3390/molecules26185563
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Calcium Compound Type and Dosage on the Properties of Acid Rennet Goat’s Milk Gels

Abstract: The aim of this study was to determine the effect of adding calcium compounds to processed goat’s milk, and on the properties of acid rennet goat’s milk gels, which are a middle product obtained in the manufacture of acid rennet cheese. The properties of the gels directly affect the quality of acid rennet cheeses. The analysis of raw goat’s milk was carried out, then acid rennet gels were produced with the addition of six different calcium compounds (chloride, citrate, bisglycinate, gluconate, lactate, and car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Texture characterizes the product’s physical properties, such as hardness, adhesiveness, and springiness, and is considered among the essential quality characteristics of fermented dairy products. The texture properties of fermented milk are related to the type of milk, heat treatment, type of starter cultures, dry matter content, and the type of additives used [ 9 , 55 ]. Fermented goat’s milk shows a soft gel and a high ability to spread the curd compared to cow’s milk [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Texture characterizes the product’s physical properties, such as hardness, adhesiveness, and springiness, and is considered among the essential quality characteristics of fermented dairy products. The texture properties of fermented milk are related to the type of milk, heat treatment, type of starter cultures, dry matter content, and the type of additives used [ 9 , 55 ]. Fermented goat’s milk shows a soft gel and a high ability to spread the curd compared to cow’s milk [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…The texture properties of fermented milk are related to the type of milk, heat treatment, type of starter cultures, dry matter content, and the type of additives used [ 9 , 55 ]. Fermented goat’s milk shows a soft gel and a high ability to spread the curd compared to cow’s milk [ 55 ]. The rheological properties and texture of fermented goat’s milk could be improved by adding strains that produce exopolysaccharides (EPS) during incubation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural milk colour appears from the reflection of light by calcium caseinate, calcium phosphate and dispersed fat globules (Pawlos et al . 2021). Removal of calcium from buffalo milk resulted in a change in appearance of milk.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the fragile texture of goat’s milk curd and the difficulty of processing it, acid curd cheese is usually produced with the addition of rennet, since the addition of this enzyme increases the hardness of the curd [ 17 ]. Moreover, our previous study [ 18 ] showed that by increasing the heat treatment temperature of the goat’s milk and adding calcium in the form of various compounds before the milk pasteurization process, the physicochemical properties of goat’s milk gel could be improved.…”
Section: Introductionmentioning
confidence: 99%